PROSPEK DAN KENDALA PENGEMBANGAN LADA DI INDONESIA - Dewa K.S Swastika; Rosmiyati Sajuti; Sri H Suhartini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2004)
Indonesia is the second largest producer after India, but the largest exporter of peper in the world. Although Indonesia is still the world’s leading pepper exporter, its share to the world market has been declining. Indonesia has to compete with other